Occurrence and larval movement of Diatraea saccharalis (Lepidoptera: Crambidae) in seed mixes of non‐Bt and Bt pyramid corn. Issue 10 (1st March 2013) - Wangila, David S; Leonard, B Rogers; Ghimire, Mukti N; Bai, Yaoyu; Zhang, Liping; Yang, Yunlong; Emfinger, Karla D; Head, Graham P; Yang, Fei; Niu, Ying; Huang, Fangneng
Abstract: BACKGROUND: Larval movement of target pest populations among Bt and non‐ Bt plants is a major concern in the use of a seed mixture refuge strategy for Bt resistance management. In this study, occurrence and larval movement of the sugarcane borer, Diatraea saccharalis (F.), were evaluated in four planting patterns of non‐ Bt and Bt plants containing Genuity® SmartStax TM traits in 2009–2011. The four planting patterns were: (1) a pure stand of 27 Bt plants; (2) one non‐ Bt plant in the center, surrounded by 26 Bt plants; (3) a pure stand of 27 non‐ Bt plants; (4) one Bt plant in the center, surrounded by 26 non‐ Bt plants. Studies were conducted under four conditions: (1) open field with natural infestation; (2) greenhouse with artificial infestations; open field with artificial infestations (3) on the center plants only and (4) on every plant. The major objective of this study was to determine whether refuge plants in a seed mixture strategy could provide a comparable refuge population of D. saccharalis to a 'structured refuge' planting. RESULTS: Larvae of D. saccharalis showed the ability to move from infested plants to at least four plants away, as well as to adjacent rows, but the majority remained within the infested row. However, the number of larvae found on the non‐ Bt plants in the mixture plantings was not significantly reduced compared with the pure stand of non‐ Bt corn. CONCLUSION: The results of this study show that refuge plants in a seed mixture may be able to provide a comparable refuge population of D. saccharalis to a structured refuge planting. © 2013 Society of Chemical Industry